Boosting Immunity and Management against Wheat Fusarium Diseases by a Sustainable, Circular Nanostructured Delivery Platform - Sara Francesconi; Riccardo Ronchetti; Emidio Camaioni; Stefano Giovagnoli; Francesco Sestili; Samuela Palombieri; Giorgio Mariano Balestra (Plants, 2023)
Fusarium head blight (FHB) and Fusarium crown rot (FCR) are managed by the application of imidazole fungicides, which will be strictly limited by 2030, as stated by the European Green Deal. Here, a novel and eco-sustainable nanostructured particle formulation (NPF) is presented by following the principles of the circular economy. Cellulose nanocrystals (CNC) and resistant starch were obtained from the bran of a high amylose (HA) bread wheat and employed as carrier and excipient, while chitosan and gallic acid were functionalized as antifungal and elicitor active principles. The NPF inhibited conidia germination and mycelium growth, and mechanically interacted with conidia. The NPF optimally reduced FHB and FCR symptoms in susceptible bread wheat genotypes while being biocompatible on plants. The expression level of 21 genes involved in the induction of innate immunity was investigated in Sumai3 (FHB resistant) Cadenza (susceptible) and Cadenza SBEIIa (a mutant characterized by high-amylose starch content) and most of them were up-regulated in Cadenza SBEIIa spikes treated with the NPF, indicating that this genotype may possess an interesting genomic background particularly responsive to elicitor-like molecules. Quantification of fungal biomass revealed that the NPF controlled FHB spread, while Cadenza SBEIIa was resistant to FCR fungal spread. The present research work highlights that the NPF is a powerful weapon for FHB sustainable management, while the genome of Cadenza SBEIIa should be investigated deeply as particularly responsive to elicitor-like molecules and resistant to FCR fungal spread.